Website Quality Evaluation of OKE Garden using WebQual, The Marketing Mix, and Importance-Performance Analysis - Nadya Kamilia Faiqoh; Popong Nurhayati; Heny Kuswanti Suwarsinah (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2026)
The rapid advancement of digital technologies has significantly impacted various service sectors, including the garden landscaping industry. In response to this development, OKE Garden has implemented a website-based e-commerce platform aimed at improving service accessibility and operational efficiency. This study seeks to evaluate the usability and service quality of this digital platform from the user’s perspective by adopting the Technology Acceptance Model (TAM) as the analytical framework. Within this framework, Perceived Ease of Use (PEOU) is assessed using WebQual 4.0 indicators, while Perceived Usefulness (PU) is measured through the four elements of the marketing mix, namely Product, Price, Place, and Promotion. To analyze the alignment between user expectations and actual service performance, the Importance-Performance Analysis (IPA) method was utilized. Data were obtained from 57 respondents in the Greater Jakarta area (Jabodetabek), primarily first-time users who had previously interacted with the OKE Garden website. Prior to analysis, the data underwent validity and reliability testing to ensure robustness. The findings show that users rated the importance of website attributes higher than their actual performance, indicating a gap that highlights areas requiring improvement. Several key indicators were identified—including ease of navigation, clarity of information, data security, and pricing strategy—which were categorized in Quadrant I (high importance, low performance), indicating areas that require immediate attention. Overall, the results suggest that although digital technology adoption has taken place, user acceptance remains suboptimal. Therefore, a more comprehensive enhancement of usability and service quality is necessary to meet user expectations and improve overall satisfaction.